Growth and development of Mentha piperita L. in nutrient solution as affected by rates of potassium - Valmorbida, Janice [UNESP]; Boaro, Carmen Sílvia Fernandes [UNESP] (Brazilian Archives of Biology and Technology, 2007)
A influência do potássio no desenvolvimento de Mentha piperita L. foi avaliada em plantas cultivadas em solução nutritiva modificada pela variação de potássio, com 6.0, 3.0 e 1.5 mmol L-1, que estabeleceram as diferenças entre tratamentos e corresponderam, respectivamente, a sua concentração proposta na solução nº 2 de Hoagland e Arnon e diminuição em 50% e 75%. Até os 21 dias após o transplante a concentração utilizada foi diluída em 50% nos três tratamentos. Avaliou-se área foliar, desenvolvimento da parte aérea e matéria secas dos diferentes órgãos. Plantas cultivadas com 1.5/3.0 mmol L-1 K apresentaram maior desenvolvimento da parte aérea. Demais variáveis não diferiram entre as plantas dos diferentes tratamentos.

The influence of potassium on the development of Mentha piperita L. was evaluated in the plants grown in nutritive solution modified by variations in potassium, at 6.0, 3.0, and 1.5 mmol L-1, establishing differences between treatments and corresponding, respectively, to the concentration proposed in Hoagland and Arnon's no. 2 solution and reductions by 50% and 75%. Until 21 days after transplanting, the concentration used was diluted to 50% in the three treatments. Evaluations consisted of leaf area, development of the above-ground part, and dry matter of different plant organs. Plants grown with 1.5/3.0 mmol L-1 K showed greater development of the above-ground part. Other variables were not different among plants in the different treatments.
Keywords: Lamiaceae; mint; leaf area; hydropony; dry matter